NET İŞLETME SERMAYESİ VE CARİ ORAN İLİŞKİSİ: BORSA İSTANBUL’DAN SEÇİLMİŞ İŞLETMELER ÜZERİNE BİR İNCELEME - (:unkn) unknown (My University, 2017)
İşletme sermayesi, işletmelerin varlıklarını sürdürmeleri, piyasadaki ko-numları ve performansları bakımından önem taşımaktadır. Net işletme sermayesi ileişletmelerin likidite durumu değerlendirilirken cari oran da dikkate alınmaktadır. Bukapsamda, Borsa İstanbul (BİST) Metal Eşya ve Makine sektöründen seçilmiş 7 işlet-menin 2009-2014 dönemindeki cari oranları ve net işletme sermayeleri hesaplanmıştır.Cari oranı 1’den büyük işletmelerin pozitif net işletme sermayesine; cari oranı 1’denküçük işletmelerin ise negatif net işletme sermayesine sahip oldukları görülmüştür. Netişletme sermayesi pozitif işletmelerin başarılarının sürmesi için aktif kalitesine ve enuygun stok düzeyine önem vermeleri gerektiği vurgulanmıştır.

Working capital is crucial with regard to the credibility and performance of companies and the maintenance of their operations. When the liquidity position of companies is evaluated, current ratio is considered as well as net working capital. In this respect, current ratios and net working capital of companies were calculated from 2009 to 2014 in the BIST Metal Products and Machinery sector. It has been observed that positive net working capital was found in companies which had a current ratio greater than 1. Moreover, it has been highlighted that these companies should focus on the optimum level of inventory and asset quality in order to maintain their success in working capital management.
The Relationship Between Net Working Capital and Current Ratio: an Analysis on Selected Companıes in Istanbul Stock Exchange
Keywords: İş; İşletme Finans; İktisat; İşletme